2024
DOI: 10.1021/acs.orglett.3c04291
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Promoted α-C(sp3)–H Amination of Ethers with Azoles and Amides

Yaqi Deng,
Zongjing Hu,
Jian Xue
et al.

Abstract: A visible-light-induced highly efficient C(sp 3 )−H amination of ethers with amides and azoles has been presented under mild conditions via a nitrogen-and carbon-centered radical coupling process. This protocol successfully utilizes 2,3-dichloro-5,6-dicyano-p-benzoquinone (DDQ) and tert-butyl nitrite (TBN) as cocatalysts to deliver the aminated products of ethers under aerobic conditions. Notably, the developed reaction features the corresponding products in good yields (up to 93%) with a wide substrate scope.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In the quenching reaction with another radical scavenger, butylated hydroxytoluene (BHT), product 4a was also suppressed completely. Nevertheless, a N 2 -selective BHT-adduct 8 could be detected by LC-MS, of which the N 2 -regioisomer structure could be deduced from our previous research result 23 (Scheme 6b and Scheme S4†). These phenomena indicated that this reaction proceeded via a radical.…”
Section: Resultsmentioning
confidence: 89%
“…In the quenching reaction with another radical scavenger, butylated hydroxytoluene (BHT), product 4a was also suppressed completely. Nevertheless, a N 2 -selective BHT-adduct 8 could be detected by LC-MS, of which the N 2 -regioisomer structure could be deduced from our previous research result 23 (Scheme 6b and Scheme S4†). These phenomena indicated that this reaction proceeded via a radical.…”
Section: Resultsmentioning
confidence: 89%